Evaluation of the therapeutic effects of led (λ627 ± 10 nm) on the initial phase of ankle sprain treatment: a randomised placebo-controlled clinical trial - de Moraes Prianti, Bruno; Novello, Giovanna Figueiredo; de Souza Moreira Prianti, Tamires; Costa, Davidson Ribeiro; Pessoa, Diego Rodrigues; Nicolau, Renata Amadei (Lasers in medical science, 2018)
Various therapies for the treatment of sprains have emerged as advances occur in biomedical engineering and photobiology. Therapy with coherent and non-coherent light is a treatment modality for various musculoskeletal injuries. The main certified phototherapy benefits are the reduction of nociceptive processes and the modulation of the inflammatory process, among others. The objective of this study was to analyse the changes caused by the use of light-emitting diodes (LED) (λ627 ± 10 nm) with an energy density of 10 J/cm 2 in 40 subjects divided into two groups (20 placebo and 20 LED). All of the volunteers had acute ankle sprains by inversion of grade II treated with the PRICE (protection, rest, ice, compression and elevation) technique and were treated for 6 days with LED therapy and LED therapy turned off (placebo). Pain assessment was performed on the 1st, 3rd and 6th days using the visual analogue scale (VAS) of pain, the McGill Pain Questionnaire and volumetry. The group treated with LED showed statistically decreased pain compared to the placebo group in both the VAS (85.79 vs 55.73%) and McGill questionnaire (83.33 vs 52.52%). The reduction of oedema in the LED group on the 3rd and 6th days after therapy was statistically superior to that in the placebo ( p < 0.0001). Based on the results of this study, treatment with LED, using the tested dose, is effective for pain and oedema in the initial phase of ankle sprains.